Antecedents of tourist food consumption: food choice motives of foreign tourists in Turkey - EKİZLER, HÜSEYİN; DURMUŞ, BERİL (My University, 2022)
Culinary or gastronomy tourism has become a rising issue nowadays. People want to discover new flavour while travelling. Food consumption is the combination of one\"s cultural, social, psychological and sensory acceptance factors and it is a very complex decision-making process. Food consumption is also associated with motivational factors which are mood, health, sensory appeal, familiarity, convenience, price and natural content. The antecedents of tourist food consumption and food choice motives of foreign tourists in Istanbul were examined. The results show that sensory appeal, mood, natural content, health content and convenience had positive and direct connection with tourist food consumption intentions. There is no statistically significant evidence to support the associations of familiarity and price with the tourist food consumption intentions.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Pazarlama; Sayısal Yöntemler; Social Sciences and Humanities; Management; Marketing; Quantitative Methods; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities; Food choice; food consumption; culinary tourism; eating behaviour; Turkish food; MOOD; INFORMATION; VISITORS; CONSUMERS; SELECTION; EXPOSURE; QUALITY; EMOTION